2022
DOI: 10.1108/jima-03-2021-0074
|View full text |Cite
|
Sign up to set email alerts
|

Halal tourism as a strategic option for South Korean tourism

Abstract: Purpose This study aims to investigate the opinion of a group of informants in Seoul – South Korea’s foremost destination – on the possibility of developing a halal tourism policy that is closer to the wishes of Muslim customers, which is also in line with Islamic principles. Design/methodology/approach This research investigated the perceptions of 17 key informants. The data was conducted through interview about the possibility of developing an industry that is more in line with the lifestyle of Muslim tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…It can be observed that South Korea had a total citations of 392 while producing only 25 publications. This makes sense given that South Korea is one of the non-Muslim countries that explores the potential of halal tourism (Marlinda et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that South Korea had a total citations of 392 while producing only 25 publications. This makes sense given that South Korea is one of the non-Muslim countries that explores the potential of halal tourism (Marlinda et al , 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the booming number of Muslim tourists around the world (Marlinda et al, 2022;GMTI, 2022), Islamic tourism is an area of research that is not adequately addressed in the literature (Ithnan & Ariffin, 2020), and the aspects that constitute this type of tourism experience are still unexplored by academics and practitioners (Sthapit, 2022). The study of these factors will help the destination tourism industries integrate marketing to build a stronger Islamic brand for Malaysia in Muslim markets.…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing number of Muslim tourists, South Korea is evolving into a "halal-friendly" destination, prompting the government to recognize the potential of halal tourism (Marlinda et al, 2022). Achieving halal-friendly status in Korea requires heightened halal awareness among employees in hotels and restaurants (Han et al, 2019).…”
Section: B Halal Food Awareness Among Non-muslim Consumersmentioning
confidence: 99%